Seawater carbonate chemistry based carbon dioxide removal: towards commonly agreed principles for carbon monitoring, reporting, and verification - Halloran, Paul R.; Bell, Thomas G.; Burt, William J.; Chu, Sophie N.; Gill, Sophie; Henderson, Cameron; Ho, David T.; Kitidis, Vassilis; La Plante, Erika; Larrazabal, Monica; Loucaides, Socratis; Pearce, Christopher R.; et al. (Frontiers in Climate, 2025)
Carbon Dioxide Removal (CDR) from the atmosphere is unavoidable if we are to meet the Paris Agreement’s goal of limiting global warming to 1.5°C, and almost certainly required to limit warming to 2°C. The ocean exchanges carbon dioxide (CO2) with the atmosphere and is a large repository of carbon that could either be partially emptied to allow more CO2 absorption or have its carbon storage capacity enhanced to allow it to remove additional CO2 from the atmosphere. Early-stage techniques exist to utilise the ocean in atmospheric CO2 removal, but typically, the atmospheric CO2 removal these techniques stimulate happens downstream of their activity. Verifying the carbon removal associated with these techniques, while critical when evaluating the approaches and pricing the removal, is challenging. This study briefly reviews the challenges associated with verifying the carbon removal associated with non-biological (abiotic) engineered marine CDR approaches, specifically Ocean Alkalinity Enhancement and Direct Ocean Carbon Capture and Storage, and presents the findings from a workshop held with interested parties spanning industry to government, focused on their collective requirements for the Monitoring, Reporting, and Verification (MRV) of carbon removal. We find that it is possible to agree on a common set of principles for abiotic marine MRV, but identify that delivering this MRV with today’s understanding and technology could be prohibitively expensive. We discuss focal areas to drive down marine MRV costs and highlight the importance of specification of MRV criteria by an ultimate regulator to stimulate investment into the required work. High-quality MRV is important to correctly price any CO2 removal, but we identify that accessibility and transparency in MRV approaches are also key in realising the broader benefits of MRV to society.